2017
DOI: 10.3390/ijerph14050508
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Ambient PM2.5 Exposure and Bladder Cancer Mortality in Taiwan

Abstract: Fine particulate matter (PM2.5) is an air pollutant that is receiving intense regulatory attention in Taiwan. In previous studies, the effect of air pollution on bladder cancer has been explored. This study was conducted to elucidate the effect of atmospheric PM2.5 and other local risk factors on bladder cancer mortality based on available 13-year mortality data. Geographically weighted regression (GWR) was applied to estimate and interpret the spatial variability of the relationships between bladder cancer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Moreover, the methylation extent was 64, 60, and 50 % among never, former, and current smokers [4]. PM 2.5 levels are higher in Southern and Central compared to Northern Taiwan [2629]. There are many heavy industries (e.g., petrochemical plants) in these areas [27, 28, 40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the methylation extent was 64, 60, and 50 % among never, former, and current smokers [4]. PM 2.5 levels are higher in Southern and Central compared to Northern Taiwan [2629]. There are many heavy industries (e.g., petrochemical plants) in these areas [27, 28, 40].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Taiwan, PM 2.5 was used as a proxy marker for PAHs [20]. PM 2.5 concentrations in northern Taiwan are lower than in central and southern areas [2629]. Because PAHs are present in both PM 2.5 and cigarette smoke, AHRR (cg05575921) methylation in smokers might be comparable with that in non-smokers exposed to PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…As early as in the 1980s, a large number of epidemiological studies abroad have shown that PM 2.5 has obvious side effects on human health [ 118 , 119 , 120 , 121 ]. The studies in China on the relationship between PM 2.5 and human health also fully proved that PM 2.5 can cause increases in the incidence of pulmonary heart disease [ 122 ], respiratory disease [ 123 ], cardiovascular disease [ 124 ], cancer [ 125 , 126 ] and other diseases, and even the death risk [ 127 , 128 , 129 ]. Long-term exposure to ambient PM 2.5 might be an important risk factor of hypertension and is responsible for significant hypertension burden in adults in China [ 130 , 131 ], and it leads to reduced lung function [ 132 , 133 ].…”
Section: Various Impacts Of Pm 25 Pollutionmentioning
confidence: 99%
“…The cohort studies reported uncertain correlations between bladder cancer and PM. Smith et al [ 48 ] and Yeh et al [ 22 ] found a positive association of air pollution and PM 2.5 with bladder cancer. However, Pedersen et al [ 23 ] did not find any such association in their study that included 15 population-based cohorts.…”
Section: Bladder Cancermentioning
confidence: 99%